’All’s well that ends’: Concluding a deanship - Eloff, I. (South African Journal of Higher Education, 2016)
This article presents an auto-ethnographic process of self-reflective writing during the transition period at the end of an academic deanship. As a career intervention strategy, the author adopted a self-guided process of writing based on the Schlossberg model for career transition. The article shows how self-reflective writing can craft a pathway for successful personal navigation towards the last phase of an academic leadership position. It focuses specifically on the latter part of a deanship, with the explicit intention of contributing to the relatively sparse literature on the exit phases of academic leadership positions. This article highlights the narratability of career counselling and the potential of autobiographicity to support career transition. Keywords: career counselling, auto-ethnography, deanship, dean, leadership, transition, education, self-reflective writing, career perspective.